Education and science: modern trends - Serebrennikova A. V., Kharlamov D. D., Polyshuk E. A., Baranov G. V., Shabaev V. G., Shabaev V. G., Grishina N. M., Gorokhov V. F., Markushevich M. V., Ivanova O. M., Bilalova L. M., Guriev E. A., Krylov S. N., Podzorova S. V., Khazykova T. S., Balashova T. A., Kim T. L., Lavryashina T. V., Okushko N. B., Ialunina E. N., Sergacheva O. M., Timopheeva A. M., Izosimova I. V., Kulik V. I., Kulik I. V. (Education and science: modern trends, 2016)
the work is devoted to actual cultural and social problem – the typology of culture. The work deals with the possible criteria of the typology and analyzes the views of cultural studies and sociology classics on the subject. Great attention is paid to the idea analysis of N.Y. Danilevsky, M. Weber, O. Spengler, N.A. Berdyaev and other thinkers. The problem of typological affiliation of Russian culture is also investigated.
Keywords: культура; Восток; Запад; culture; тип культуры; культурно-исторический тип; culture type; cultural and historical type; West; East